Pengaruh mind mapping terhadap motivasi dan hasil belajar PAI dan Budi Pekerti - Anisa Yusilafita; Mawardi Lubis; Desy Eka Citra Dewi (Universitas Pendidikan Indonesia, 2026)
Learning methods play an important role in encouraging student motivation; therefore, innovative, student-focused methods are needed. This study aims to examine the effect of the mind-mapping method on the motivation and learning outcomes of Pendidikan Agama Islam (PAI) dan Budi Pekerti students in grade XI at SMAN 9, Bengkulu City. This study used a quantitative experimental design involving 61 students as samples divided into experimental and control groups. Data were collected through tests and questionnaires, then analyzed using t-tests and linear regression. The results showed that the mind-mapping method significantly increased student motivation and learning outcomes compared to conventional methods. The experimental group that implemented mind mapping obtained a higher average score. These findings confirm that mind mapping is effective in facilitating structured information processing, increasing cognitive engagement, and shifting the learning paradigm toward a student-centered approach. Mind mapping is recommended as an effective pedagogical strategy to deepen understanding of complex PAI dan Budi Pekerti material and improve student academic outcomes at the secondary school level.